Effectiveness of Short-term Cardiac Rehabilitation on Clinical Manifestations in Post-MI Patients - Sh Davoodvand (MSc.); N Elahi (MSc.); M Haghighizadeh (MSc.) (Tehran University of Medical Sciences, 2009)
Background & Aim: Cardiac rehabilitation is one of the most effective ways of secondary prevention in patients with myocardial infarction manifestations. This study aimed to assess the effectiveness of cardiac rehabilitation on clinical manifestations of myocardial infarction in post-MI patients. Methods & Materials: In this interventional study, 66 patients (58 males and eight females) with myocardial infarction who were hospitalized in public hospitals of Ahwaz were selected using purposeful sampling. The participants were randomly allocated into intervention and control groups. Data was collected using a self-structured valid and reliable instrument. The intervention group participated in an 8-week cardiac rehabilitation program. Data on the clinical manifestations were collected eight weeks later. Data were analyzed in SPSS. Results: The results showed that there was significant differences between two groups in hypertension crisis (P=0.03), chest pain, dyspnea, fatigue and palpitation after the cardiac rehabilitation (P<0.001). Conclusion: Cardiac rehabilitation program decreased the clinical manifestations of myocardial infarction in post-MI patients. It is recommended to perform this procedure in the post-MI patients.   Key words: cardiac, rehabilitation, myocardial infarction, clinical manifestations